Prevalência da síndrome metabólica em pacientes com psoríase atendidos em um Hospital Universitário - Nunes, Ana Claudia Palitot de Oliveira Lima (2024)
The prevalence of psoriasis, a lifelong immune-mediated inflammatory skin disease, has increased worldwide, and metabolic syndrome (MetS), a condition that brings together important risk factors, has been frequently observed in these individuals. There is consensus in the literature that patients with immune-mediated pathologies present with chronic inflammation, similar to that found in metabolic disorders. Considering the growing number of individuals with MS and psoriasis, as well as the limited evidence capable of explaining the possible mechanisms involved in the coexistence of these diseases, this research aimed to determine the prevalence of MS in patients with psoriasis and associate it with other risk factors. This is a cross-sectional study, part of the project entitled “Effect of supplementation with megadose of vitamin D3 on inflammatory markers, oxidative stress, and influence of the rs4516035 and rs731236 polymorphisms of the VDR gene in patients with psoriasis” which was approved by the research committee in research ethics at the Lauro Wanderley University Hospital (HULW). The study included 146 patients who attended a dermatological consultation at the Paraíba Psoriasis Support and Treatment Reference Center and met the following eligibility criteria: clinical diagnosis of psoriasis and without the following conditions: thyroid or autoimmune disease, malignant neoplasms, active tuberculosis, pregnant and lactating women. Personal, demographic, clinical and lifestyle aspects, physical activity, anthropometry, food consumption and specific laboratory tests were collected: fasting blood glucose (FG), total cholesterol (TC) and fractions, triglycerides (TG), 25 hydroxyvitamin D (25(OH) D), parathyroid hormone (PTH), calcium (Ca), alanine aminotransferase (TGP), glutamate oxaloacetic transaminase (TGO), urea and creatinine and, subsequently, the classification of MS was made. The results were considered statistically significant if p < 0.05. As a result of this research, a significant prevalence of MS was found in patients with psoriasis and other risk factors. A difference between the means was found in relation to MS and body mass index (BMI), with significantly higher values being found in individuals with psoriasis and MS, (P < 0.001), when compared to the group without the condition, highlighting that overweight and obesity are very common in these individuals. Age was associated with this coexistence (P < 0.001). In relation to sex, men presented a higher risk in terms of waist circumference (WC), (P < 0.014), when compared to women, suggesting that male individuals present a higher cardiovascular risk in the studied population. Furthermore, the percentage of overweight and obese individuals in the sample was 78.8%, with this group showing associations with other cardiovascular risks, such as: WC, systolic blood pressure (SBP), diastolic blood pressure (DBP), TG, high-density lipoprotein (HDL), GJ and with urea and the enzyme alanine aminotransferase (TGP). A regression test identified that WC was the most predictive risk factor for this condition in the studied population, showing that overweight and obesity must be combated in these patients.